Upaya Pemerintah Desa dalam Meningkatkan Kualitas Pelayanan Publik - Selvi Dian Safitri; Yaqub Cikusin; Hayat Hayat (CV. Publikasi Indonesia, 2022)
This study aims to determine the efforts of the village government in improving the quality of public services, especially in the field of population administration at the Panji Kidul Village Office, Situbondo Regency, to find out the supporting factors and also the inhibiting factors of the village government's efforts to improve the quality of public services. The method used in this research is a descriptive research method with a qualitative approach, namely by describing events that occur in the field, data collection will be carried out using interview, observation, and documentation techniques. The results of the study indicate that the village government's efforts to improve the quality of public services in the field of population administration at the Panji Kidul Village Office are by motivating employees related to work discipline, improving the quality and professionalism of employees, improving facilities and infrastructure, the existence of procedures for the order of population administration services, improving performance. government apparatus. In addition, the participation of rural communities in public services is also very helpful in the smooth process of public services. The supporting factors for the village government's efforts to improve the quality of public services in the field of population administration at the Panji Kidul Village Office are community participation, cohesiveness between village government officials, and the determination of service costs. The inhibiting factors are the quality of village government apparatus resources, limited facilities and infrastructure, and undisciplined working conditions.